(untitled) (Raparin Journal of Humanities (RJH), 2024)
This study is entitled (The Semiology of Title Poeticness in Jabar Jamal Gharib’s "The flying Birds that are Dross" novel). The study attempts to shed light on an essential and influential subject which is the semiology of title poeticness. It introduces the term and concept of semiology of title poeticness and its value as a semiological icon within a broad genre like novel. There has not been much research in Kurdish literary works aimed at presenting the role and position of semiology of title poeticness in the genre of novel. Hence، the current study highlights the hidden aspects of semiology of title poeticness، that is، it uncovers the meanings behind the masks of the titles at each level of morphology، syntax، rhythm and melody and meaning within the above-mentioned novel. The poetic titles are semiologically interpreted in order to highlight the writer’s message behind the iconicity of the poetic-like titles.